Pengaruh Tingkat Responsivitas Pemerintah Daerah terhadap Kepuasan dalam Penanganan Pengaduan Masyarakat pada Kanal Sambat Online Kota Malang - Muhammad Farrel Langit Arundaya; Muhammad Farid Ma'ruf; Fitrotun Niswah; Galih Wahyu Pradana (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This study aims to analyze the effect of local government responsiveness in handling online public complaints through SAMBAT Online on community satisfaction. The research employed a quantitative approach with a causal associative design. Data were collected from 90 respondents who had previously used SAMBAT Online services. Data analysis techniques included descriptive statistics, instrument testing, classical assumption tests, simple linear regression, t-test, and coefficient of determination analysis using SPSS version 25. The results indicate that the responsiveness level of the Malang City Government is categorized as moderate with a percentage score of 64.09%, while community satisfaction is categorized as high with a score of 69.96%. Simple linear regression analysis revealed that responsiveness has a positive and significant effect on community satisfaction, indicated by a significance value of 0.000 0.05 and a coefficient of determination (R²) of 0.524. This finding suggests that government responsiveness contributes 52.4% to community satisfaction, while the remaining 47.6% is influenced by other factors outside the research model. The study concludes that responsiveness is a crucial determinant in improving public satisfaction with digital complaint services.